What makes a great journal great in economics?: The singer not the song - Chang, C.; Mcaleer, M.; Oxley, Leslie (2011)
This paper analyses what makes a great journal great in economics. Alternative research assessment measures (RAM) are discussed, with an emphasis on the Thomson Reuters Institute for Scientific Information (ISI) Web of Science database. ISI RAM that are calculated annually or updated daily are defined, including the classic 2-year impact factor (2YIF), 5-year impact factor (5YIF), immediacy (zero-year impact factor (0YIF)), eigenfactor score, article influence, citation performance per paper online, h-index, Zinfluence, PI-BETA (papers ignored - by even the authors) and two new RAM measures, self-citation threshold approval rating and impact factor inflation. The data are analysed for the most highly cited journals in economics, management, business and business-finance on the basis of 2YIF. In addition to evaluating research in the most highly cited journals in economics, management, business and business-finance, the paper evaluates alternative RAM, highlights similarities and differences in RAM criteria, finds that several RAM capture similar performance characteristics, and finds that immediacy and PI-BETA are not highly correlated with other RAM. Harmonic mean rankings of the 12 RAM criteria are also presented. Emphasizing 2YIF to the exclusion of other useful RAM criteria can lead to a distorted evaluation of journal performance and influence. © 2010 Blackwell Publishing Ltd.